Chinese Scholars on Western Ideas about Thinking, Leadership, Reform and Development in Education - Chen, Sylvester; Kompf, Michael; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
This collection of papers by a group of Chinese educational administrators came about through a graduate study program that facilitated comparisons of educational practices from other cultures against the backdrop of globalization. Collaborative international programs allow contrast and comparisons of practices, policies and educational principles but are not without barriers faced by candidates which can include but are not limited to culture shock and communication and language adjustments. Comparisons of international educational institutions are telling when examined through transfer credit policies, degree recognition, institutional accreditation and the value of academic credits in a globalized educational marketplace. China and Chinese educators recognize that movement and take it most seriously as demonstrated by the group of educational ambassadors who have contributed a variety of perspectives and interests to this volume. They are a new wave of thinkers whose studies embrace their native culture and open minds to alternative ways of understanding and acting on rapidly changing educational circumstances for learners, teachers and administrators.
Keywords: Education; Education; Education (general).